STRATEGI MASKAPAI PENERBANGAN MENGHADAPI KETERPURUKAN PARIWISATA DI MASA PANDEMI COVID-19 - I Made Budiasa; I Wayan Nurjaya (Universitas Triatma Mulya, 2022)
This study tended to determine the airlines strategy taken by its management in facing the downturn tourism in the Word due to Covid 19 pandemic. The research used descriptive qualitative analysis while data collected by study documentation and online interviews. There are SO strategy such as (a) growth strategy in the form of concentration through vertical integration (forward integration: increasing control over distributors and backward: increasing control over suppliers), (b) Product development: creating product innovations that are more attractive to prospective passengers, (c) Market penetration: Increasing market share for current products by opening domestic routes that have been discontinued due to Covid-19, (d) Market development: Introducing current products to a new geographic area; In the ST strategy, they are (a) resource management by implementing cost effectiveness and efficiency in various possible fields without violating applicable regulations, (b) market development by carrying out promotions in various forms, (c) product development by making various product innovation that might be more attactive to prospective passengers. The WO Strategy includes (a) Resource management: Carrying out cost effectiveness and efficiency in various possible fields without violating applicable regulations, (b) Increasing focus on cargo transportation other than passengers, (c) Increasing focus on domestic passenger transportation on required routes; while the WT's Strategy are (a) Stopping operations temporarily until the number of prospective passengers increases. (b) Declaring failed (bankrupt) because the company could not run any longer.